2023
DOI: 10.1021/acs.energyfuels.3c03004
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Carbon Dioxide Sequestration in Deep Unmineable Coal Seams Using CO2-ECBM Technology: Experimental Studies, Simulation, and Field Applications

Grant Charles Mwakipunda,
Yuting Wang,
Melckzedeck Michael Mgimba
et al.

Abstract: CO 2 -enhanced coalbed methane (CO 2 -ECBM) technology helps to store CO 2 while producing a clean source of energy (CH 4 ) through the sorption process. This technique can sequester much CO 2 at low temperatures and pressures while recovering CH 4 , which will help offset the associated costs, such as capturing injection gases, drilling and completion infrastructure, compression, and injection expenses. This review paper critically analyzes the CO 2 sequestration potentiality in deep unmineable coal seams. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 201 publications
0
2
0
Order By: Relevance
“…With the depletion of shallow resources, coal mining is gradually marching to deep areas. The occurrence conditions of deep coal seams are complicated, such as high ground stress, high gas, high heterogeneity, low permeability, low strength, and multiple structures, which undoubtedly increase the difficulty of gas control in coal mines in China. As an effective means to prevent and control coal and gas outbursts, hydraulic antireflection technology (hydraulic fracturing, hydraulic punching, and hydraulic cutting) has been gradually promoted in China since the 1960s and has achieved good control effects. …”
Section: Introductionmentioning
confidence: 99%
“…With the depletion of shallow resources, coal mining is gradually marching to deep areas. The occurrence conditions of deep coal seams are complicated, such as high ground stress, high gas, high heterogeneity, low permeability, low strength, and multiple structures, which undoubtedly increase the difficulty of gas control in coal mines in China. As an effective means to prevent and control coal and gas outbursts, hydraulic antireflection technology (hydraulic fracturing, hydraulic punching, and hydraulic cutting) has been gradually promoted in China since the 1960s and has achieved good control effects. …”
Section: Introductionmentioning
confidence: 99%
“…Carbon capture and storage (CCS) is considered an effective and scientifically proven technique for reducing anthropogenic CO 2 emissions in a safe manner. This approach involves the injection of captured CO 2 into suitable subsurface geological formations, such as saline aquifers and depleted oil/gas reservoirs. The secure confinement of CO 2 within these geological media is facilitated through various trapping mechanisms, including residual trapping, structural trapping, dissolution trapping, and mineral trapping. Notably, shale formations and unmineable coal seams have also been tested for their suitability for geological storage of CO 2 . Coal seams and shales can trap enormous volumes of CO 2 via adsorption trapping. , Particularly, the injection of CO 2 into the coal seams has been receiving increasing attention due to its dual advantages in geological CO 2 storage and enhanced coalbed methane (ECBM) recovery. Coal seams have also been tested for their suitability for hydrogen (H 2 ) storage in the context of the transition toward clean energy . Indeed, studies have shown the potential of H 2 adsorption in coals as well, albeit much lower than CO 2 . , …”
Section: Introductionmentioning
confidence: 99%